Peran Gaya Hidup, Kesadaran Merek dan Kualitas Rasa terhadap Revisit dengan Moderasi Kualitas Pengalaman - Surya Bintarti; Ergo Nurpatria Kurniawan; Wini Nur Kusti’ah (Departement of Mathematics Education, 2023)
This study aims to examine the relationship between the influence of lifestyle, brand awareness, taste quality on repurchase intention which is moderated by the quality of experience. Bekasi. So the collection of this population is non-probability sampling and the technique of taking respondents is purposive. Purposive sampling can be understood as a sampling technique with certain considerations. Research was processed using a regression technique, which was processed using SmartPLS. 1) Lifestyle of consumers of Prima mineral water products will encourage repurchase intention, 2) Brand awareness of Prima mineral water products does not support repurchase intention, 3) Quality of consumer taste of Prima mineral water products supports repurchase interest, 4) Quality of experience performs the role of moderating lifestyle on, 5) Quality of experience performs the role of moderating brand awareness on repurchase intention, 6) Quality of experience performs the role of moderating the role of taste quality on purchase intention.